2014
DOI: 10.1353/cpr.2014.0007
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling Traditional Knowledge, Food Security, and Climate Change: Experience From Old Crow, YT, Canada

Abstract: Community concern is high and favored adaptation options include agriculture, improved food storage, and conservation through increased traditional education. These results were presented to the community for review and revision, after which the Vuntut Gwitchin Government will integrate them into its ongoing adaptation planning measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 3 publications
0
32
0
1
Order By: Relevance
“…Nichols et al 2004, Magga et al 2009, Douglas et al 2014. These forums also provided a way to develop research topics and define priorities that could prove useful to local knowledge users and policymakers (e.g Ford et al 2007, Doyle et al 2013…”
mentioning
confidence: 99%
“…Nichols et al 2004, Magga et al 2009, Douglas et al 2014. These forums also provided a way to develop research topics and define priorities that could prove useful to local knowledge users and policymakers (e.g Ford et al 2007, Doyle et al 2013…”
mentioning
confidence: 99%
“…If noted, this information was in the background to the research (n = 16/39) [ 44 58 ] the method section (n = 29/39) [ 47 , 48 , 50 52 , 54 , 55 , 57 , 59 79 ], and/or in the results section (n = 3/39) [ 59 , 74 , 80 ] of the articles. A number of diverse ways were employed to identify the role of the local or regional Indigenous governing organization in the research including the development of a research or advisory board [ 55 , 65 , 75 , 77 , 81 ]; identifying research as a ‘collaboration’ or ‘partnership’ with an Indigenous organization or government [ 44 , 46 , 48 , 50 , 51 , 55 , 56 , 61 , 62 , 66 , 73 , 76 , 79 , 82 ]; and/or noting a workshop was hosted to engage or share information with the Indigenous government or organization [ 52 , 62 , 63 ]. Of the articles that detailed the role of community in the research, 33% (n = 13/39 articles) explicitly indicated that the research was community-initiated or community-led [ 46 , 48 , 51 , 53 , 55 , 57 , 60 , 65 , 67 , …”
Section: Resultsmentioning
confidence: 99%
“…A number of diverse ways were employed to identify the role of the local or regional Indigenous governing organization in the research including the development of a research or advisory board [ 55 , 65 , 75 , 77 , 81 ]; identifying research as a ‘collaboration’ or ‘partnership’ with an Indigenous organization or government [ 44 , 46 , 48 , 50 , 51 , 55 , 56 , 61 , 62 , 66 , 73 , 76 , 79 , 82 ]; and/or noting a workshop was hosted to engage or share information with the Indigenous government or organization [ 52 , 62 , 63 ]. Of the articles that detailed the role of community in the research, 33% (n = 13/39 articles) explicitly indicated that the research was community-initiated or community-led [ 46 , 48 , 51 , 53 , 55 , 57 , 60 , 65 , 67 , 71 , 80 , 81 , 83 ]. Community-initiated or -led was described as awarding the research funding to a local Indigenous government [ 53 , 60 ], the principal investigator being the local Indigenous government [ 46 ], or a collaboration resulting from a previous working relationship between the academic researchers and the community [ 46 , 51 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, studies which take into account traditional knowledge now seem to have gained more importance in research to better understand Arctic change and adaptation to it (e.g. Riedlinger and Berkes 2001;Maynard et al 2010;Douglas et al 2014;Cuerrier et al 2015;Vinyeta and Lynn 2013;Golden et al 2015). Also, special attention in this literature has been placed on recognising the impacts to indigenous communities and institutional frameworks related to strategies to deal with the impacts, such as community-based adaptation strategies and participatory planning (Tremblay et al 2008;Hovelsrud and Smit 2010;Pearce et al 2012;Champalle et al 2015).…”
Section: Societal Impactsmentioning
confidence: 99%